(untitled) (Journal of Parents and Teachers, 2025)
Jesús Garrido distinguishes between efficient and effective students. While efficient students are those who get a lot done, effective students are those who are able to organise their time, concentrate, are responsible, persistent and able to correct their mistakes. The author explains different ways to promote effectiveness in pupils, such as avoiding false praise, punishment, helping students too much, etc.